If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 4) + -1(3 + 2b) = 11 Reorder the terms: 3(4 + b) + -1(3 + 2b) = 11 (4 * 3 + b * 3) + -1(3 + 2b) = 11 (12 + 3b) + -1(3 + 2b) = 11 12 + 3b + (3 * -1 + 2b * -1) = 11 12 + 3b + (-3 + -2b) = 11 Reorder the terms: 12 + -3 + 3b + -2b = 11 Combine like terms: 12 + -3 = 9 9 + 3b + -2b = 11 Combine like terms: 3b + -2b = 1b 9 + 1b = 11 Solving 9 + 1b = 11 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 1b = 11 + -9 Combine like terms: 9 + -9 = 0 0 + 1b = 11 + -9 1b = 11 + -9 Combine like terms: 11 + -9 = 2 1b = 2 Divide each side by '1'. b = 2 Simplifying b = 2
| x+5=(x^2+x-2)/2 | | 2x+1/3x-2=9/10 | | 3x-5=15-x | | 3kx^2+(k-5)x=5x^2+2 | | 3x+3y=10.74 | | s+s-19=17 | | (6/5)+(((5/3)+(2/3)-(3/2))/(7*((1/3)-(1/2)))) | | x+3=12-x | | 12-3x=17x | | 3y+13=7 | | 4+10x=103+3 | | 6x+4y=18.90 | | p=50-q | | 5x-1.2y=9 | | 29=5a+4 | | 2w^2-9w=0 | | (4-3x)log(3)=(x+5)log(4) | | 2(9n-1)+7(n+6)=20 | | 4x^2+2x+1=x^2+4x+4 | | x^2+2x+1-3x^2+6x-3=6 | | 136x-15*(x+0.5)-83x= | | 5(p+4)=25+(7-p) | | 136x-15*(x+0.5)= | | x^2+4x+4+x^2-3x=1 | | 15*(x+0.5)= | | x^2-6x+9=44-11x | | 4X^2+10X=-X^2-X+4 | | -5-3x=12 | | 3q+4=4q-1 | | 0=3x^2-17x-66 | | 9b+8=1 | | 5-9m=3 |